Proccedings of 10th International Conference "Environmental Engineering" 2017
DOI: 10.3846/enviro.2017.147
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Crumb Rubber on Modified Bitumen Properties

Abstract: Abstract. Rubber derived from grinding of recycled cars and trucks tyres may be successfully used as a bitumen modifier. Number of researches reported sufficient characteristics of rubber modified asphalt binders or modified asphalt mixes in terms of improved permanent deformation and fatigue cracking. The behavior of crumb rubber asphalt binders depends on several factors, such as modification method, rubber content and size, modification temperature, mixing speed and time applied during the digestion process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Zolfaghari et al [6] investigated the effect of different sizes of tyre rubber crumbs on bitumen and concluded that reducing the size of crumb rubber enhances the penetration value of bitumen. Similarly, Sernas et al [7] examined the impact of rubber content on bitumen properties using different rubber content percentages and bitumen grades. Their findings demonstrated that an increase in rubber content improves penetration Sustainability 2023, 15, 9298 2 of 11 resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Zolfaghari et al [6] investigated the effect of different sizes of tyre rubber crumbs on bitumen and concluded that reducing the size of crumb rubber enhances the penetration value of bitumen. Similarly, Sernas et al [7] examined the impact of rubber content on bitumen properties using different rubber content percentages and bitumen grades. Their findings demonstrated that an increase in rubber content improves penetration Sustainability 2023, 15, 9298 2 of 11 resistance.…”
Section: Introductionmentioning
confidence: 99%